The Association of CYP17A1, CYP19A1, and SHBG Gene Polymorphisms in Polycystic Ovary Syndrome Susceptibility: A Systematic Review and Meta-Analysis - Xing, Chuan; Zhao, Han; Zhang, Jiaqi; He, Bing (Frontiers in Physiology, 2022)
Objective: To elucidate the relationship between CYP17A1/CYP19A1/SHBG gene polymorphisms and PCOS susceptibility. Methods: We searched multiple databases from inception to December 2020 and meta analysis was conducted to elucidate the relationship between gene polymorphisms and PCOS risk. Results: 26 studies were included, comprising 4860 PCOS and 4043 controls. CYP17A1 rs743572 polymorphisms were found to be negatively associated with PCOS risk under dominant model (p = 0.017, OR = 0.83, 95%CI 0.72–0.97, I2 = 74.80%, Pheterogeneity = 0.000) in the general population while neither CYP19A1 rs2414096 polymorphisms (p = 0.578, OR = 0.87, 95%CI 0.54–1.41, I2 = 95.90%, Pheterogeneity = 0.000) nor SHBG rs6529 polymorphisms (p = 0.752, OR = 0.99, 95%CI 0.94–1.05, I2 = 60.90%, Pheterogeneity = 0.012) was associated with PCOS susceptibility under dominant model in the general population. Conclusion: CYP17A1 rs7435721 polymorphisms might be protective factors against PCOS in general populations. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD4202122640.